The Effect of Retelling Story Towards Students’ Speaking Ability - D, Darwissyah Irwan (Universitas Islam Negeri Raden Intan Lampung, 2016)
Speaking is the ability to use language to express their feeling, ideas, and opinion and for communication between speaker and listener. Speaking is so much a part of daily life that we take it from granted. Speaking is one of the language skills that should be learnt and mastered. The students learn to communicate each other by using the language they learn. There are some problems in speaking class of MA Al-Asy’ariyah Bandar Lampung when the writer did the preliminary research. They get difficulty to express their ideas in English. They were reluctant to express or communicate in English. They were rarely practicing speaking. They were not motivated to practice speaking. They also feel bored with teaching learning process. The objective of this research is to know the implementation of retelling story in teaching speaking towards students’ speaking skill at the first semester of eleventh class of MA Al-Asy’ariyah Bandar Lampung. In conducting the research, the writer used experimental method and the populating of this research were 28 students at the first semester of the eleventh class at MA Al-Asy’ariyah Bandar Lampung 2011/2012. In this research the writer used pre test and post test the sample of these research 28 students. In taking the sample the writer used total sampling technique, it involved one class. In the data collecting technique the writer used speaking test by using retelling story. After analyzing the data by using t test formula, it was found that t ratio > t table with significant level 5% that 3,82 > 2,00. It means that t ration > t table, so there is the significant students speaking skill.